Exploring the Climate Change Impact on Major Food Crops of Bangladesh - A Time Series Analysis - Rabbi, Md Mursalin Hossain; Tabassum, Nazia (International Journal of Sustainable Agricultural Research, 2020)
This paper tries to explore the dynamic relationship between the yield of major crops in Bangladesh (aus, amas, boro, wheat and potato) and climate change (average rainfall, average maximum temperature and average minimum temperature). Graphical visualization shows that, there is increasing trend in average annual minimum temperature and average annual minimum rainfall, while there is decreasing trend of average annual maximum temperature. We applied autoregressive distributive lag (ARDL) cointegration method in order to study the dynamic relationship. The paper finds long run dynamic link between yield of aus rice and average rainfall and average minimum temperature. We have found short run dynamic relationship for yield of aman rice, boro rice and potato. However, we do not find any dynamic relationship has been found for yield of wheat with the variables of climate change. After estimation the dynamic relationship, we ensure there is no serial correlation among residuals using Breusch-Godfrey test and models are normally distributed using histogram and Jarque-Bera test. Finally, we ensure the stability of the models applying CUSUM test.